Answer:
4
Step-by-step explanation:
1+5+6-1-7
12-8
4
I think that's it
I believe its Alan, because I multiplied 5,280x21 and got 15,840 and then I divided that by 60, and got 258. 258≤1750... so Alan is you're answer
Answer:
y = -3x - 1
Step-by-step explanation:
y = mx + c
m = (-4-2)/(1-(-1)) = -6/2 = -3
y = -3x + c
When x = -1, y = 2
2 = -3(-1) + c
c = 2 - 3 = -1
y = -3x - 1
Answer:
C. 5x² - 4
General Formulas and Concepts:
<u>Algebra I</u>
- Composite Functions
- Combining Like Terms
Step-by-step explanation:
<u>Step 1: Define</u>
f(x) = 4x² + 1
g(x) = x² - 5
(f + g)(x) is f(x) + g(x)
<u>Step 2: Find (f + g)(x)</u>
- Substitute: (f + g)(x) = 4x² + 1 + x² - 5
- Combine like terms: (f + g)(x) = 5x² - 4